2021
DOI: 10.1101/2021.04.25.21256067
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trends of SARS-CoV-2 antibody prevalence in selected regions across Ghana

Abstract: To estimate the level of community exposure to SARS–CoV–2 in Ghana, we conducted phased seroprevalence studies of 2729 participants in selected locations across Ghana. Phase I screening (August 2020) covered a total of 1305 individuals screened at major markets/lorry stations, major shopping malls, hospitals and research institutions involved in COVID–19 work. The screening was performed using a strip–in–cassette lateral flow type Rapid Diagnostic Test (RDT) kit that simultaneously and separately detected IgM … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 38 publications
(47 reference statements)
3
14
0
1
Order By: Relevance
“…Nwosu et al [ 131 ] reported an antibody seroprevalence of up to 30% from sampling over 900 persons in Yaounde district, Cameroon, and this was more than 300 times the reported national case count from PCR testing. A study in Ghana with rapid kit detection of anti-nucleocapsid protein IgG and IgM reported up to 27% antibody seropositivity in populated areas such as lorry stations and markets, as compared to 10% seropositivity in shopping malls mostly patronized by the affluent [ 132 ], and these are much more than the reported infection rate from national case counts. A study among healthcare workers in Kenya found up to 20% IgG seropositivity against the SARS-CoV-2 spike protein in highly populous regions and about half that level of seropositivity in less populated areas [ 133 ].…”
Section: Covid-19 Seroepidemiology In Africa and The Effect Of Co-inf...mentioning
confidence: 99%
“…Nwosu et al [ 131 ] reported an antibody seroprevalence of up to 30% from sampling over 900 persons in Yaounde district, Cameroon, and this was more than 300 times the reported national case count from PCR testing. A study in Ghana with rapid kit detection of anti-nucleocapsid protein IgG and IgM reported up to 27% antibody seropositivity in populated areas such as lorry stations and markets, as compared to 10% seropositivity in shopping malls mostly patronized by the affluent [ 132 ], and these are much more than the reported infection rate from national case counts. A study among healthcare workers in Kenya found up to 20% IgG seropositivity against the SARS-CoV-2 spike protein in highly populous regions and about half that level of seropositivity in less populated areas [ 133 ].…”
Section: Covid-19 Seroepidemiology In Africa and The Effect Of Co-inf...mentioning
confidence: 99%
“… Overall seroprevalence of SARS-CoV-2 antibodies in Africa [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. …”
Section: Figureunclassified
“…We also assumed that for the base case scenario, at the beginning of the simulation, I =1, A=0, P=0, D=0, and V=0. We accounted for the age-specific seroprevalence of SARS-CoV-2 using estimates from Quarshie and colleagues in August 2020 ( 31 ). We, therefore, assumed that 17.5% of persons below 25 years, 43.6% of those between 25-64 years, and 18% of 65+ persons had been infected at the beginning of the simulation.…”
Section: Supplementary Text: Methodsmentioning
confidence: 99%
“…Studies on COVID- 19 vaccine hesitancy among Ghanaians reported that more than 35% of participants said they would not receive the vaccine because of concerns about vaccine efficacy and conspiracy theories ( 7, 10 ). Moreover, a seroprevalence study found that 19% of Ghanaians tested positive to anti-SARS-CoV-2 IgM or IgG or both in August 2020 ( 11 ). Thus, a majority of Ghanaians may be susceptible, and insight to effectively prioritize dispensation of limited vaccines would be the best approach to mitigating the pandemic.…”
Section: Introductionmentioning
confidence: 99%